2018
DOI: 10.1038/s41929-018-0029-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic asymmetric synthesis of the metallo-β-lactamase inhibitor aspergillomarasmine A and related aminocarboxylic acids

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 27 publications
1
57
0
Order By: Relevance
“…Recently, we reported that ethylenediamine-N,N 0 -disuccinic acid (EDDS) lyase naturally catalyzes a reversible two-step sequential addition of ethylenediamine (2) to two molecules of fumaric acid (3), giving (S)-N-(2-aminoethyl)aspartic acid (AEAA, 4) as an intermediate and (S,S)-EDDS (5) as the final product (Table 1A). 12 EDDS lyase was subsequently found to have broad substrate promiscuity, [13][14][15] accepting a wide range of amino acids with terminal amino groups (6a-k) for regio-and stereoselective addition to fumarate, thus providing a straightforward biocatalytic method for the asymmetric synthesis of AMA (1a), AMB (1b), and related aminocarboxylic acids (1c-k, Table 1B). 13 To further explore the substrate scope of EDDS lyase, as well as to prepare a small library of EDDS derivatives as potential NDM-1 inhibitors, 16 we here describe the EDDS-lyase catalyzed reaction of fumaric acid with various diamines containing different aliphatic linkers between the two amino functional groups (7a-i) ( Table 2).…”
mentioning
confidence: 99%
“…Recently, we reported that ethylenediamine-N,N 0 -disuccinic acid (EDDS) lyase naturally catalyzes a reversible two-step sequential addition of ethylenediamine (2) to two molecules of fumaric acid (3), giving (S)-N-(2-aminoethyl)aspartic acid (AEAA, 4) as an intermediate and (S,S)-EDDS (5) as the final product (Table 1A). 12 EDDS lyase was subsequently found to have broad substrate promiscuity, [13][14][15] accepting a wide range of amino acids with terminal amino groups (6a-k) for regio-and stereoselective addition to fumarate, thus providing a straightforward biocatalytic method for the asymmetric synthesis of AMA (1a), AMB (1b), and related aminocarboxylic acids (1c-k, Table 1B). 13 To further explore the substrate scope of EDDS lyase, as well as to prepare a small library of EDDS derivatives as potential NDM-1 inhibitors, 16 we here describe the EDDS-lyase catalyzed reaction of fumaric acid with various diamines containing different aliphatic linkers between the two amino functional groups (7a-i) ( Table 2).…”
mentioning
confidence: 99%
“…[21] Wild-type EDDS lyase has a large amine scope, including linear monoand diamines, and its preparative usefulness was recently demonstrated in the chemoenzymatic synthesis of aspergillomarasmine A (AMA), an important metallo-β-lactamase inhibitor, as well as various related aminocarboxylic acids. [22] Cycles are versatile and important structural moieties present in organic molecules, which act as good modifiers of properties and biological activities. [23][24][25][26] Functionalization of amino acids with cycles is a subject of great interest, leading to a diversity of useful noncanonical amino acids with broad applications.…”
mentioning
confidence: 99%
“…[30][31][32][33] Previous studies on EDDS lyase revealed that this CÀ N lyase, when working in reverse, accepts a wide variety of amino acids and diamines as substrates in the hydroamination of fumarate, giving rise to a large number of useful aminocarboxylic acid products, including biodegradable metal chelators and potent metallo-βlactamase inhibitors. [21,22] Hence, EDDS lyase is a powerful synthetic tool that nicely complements the rapidly expanding toolbox of biocatalysts for asymmetric synthesis of unnatural amino acids. In contrast to its broad amine scope, EDDS lyase was found to be specific for fumarate, and not capable to accept fumaric acid monomethyl ester, crotonic acid, mesaconic acid, itaconic acid, 2-pentenoic acid or glutaconic acid as alternative substrate for hydroamination.…”
mentioning
confidence: 99%
“…However, the intrinsic incompatibility between enzymatic and chemical catalysis challenged the combination of them in one‐pot process at the same reaction condition. For example, as a typical type of chemical catalysts focused on by this review, metal catalysts usually perform efficiently at harsh conditions such as the use of organic solvents or high temperature and pressure, whereas most enzymatic reactions occur under mild conditions, such as neutral pH, aqueous solution, and ambient temperature and pressure . Direct employment of enzyme and metal catalysts in one‐pot reactions may cause mutual inactivation of catalysts.…”
Section: Introductionmentioning
confidence: 99%